A Novel Mechanism of Modulation of 5-HT3A Receptors by Hydrocortisone - Corradi, Jeremias (2011)
Modulation of Cys-loop receptors by steroids is of physiological and therapeutical relevance. Nonetheless, its molecular mechanism has not been elucidated for serotonin (5-HT) type 3 receptors. We deciphered the mechanism of action of hydrocortisone (HC) at 5-HT type 3A receptors. Single-channel currents from the high-conductance form (∼4.7 pA, −70 mV) appear as a series of long opening events forming bursts, which group into long clusters. Although they are very infrequent, subconductance events (∼2.4 pA) are detected within clusters. HC produces a significant concentration-dependent reduction in open and burst durations, demonstrating open-channel block. In addition, it increases the appearance of subconductance levels in a concentration- and slightly voltage-dependent manner. The amplitude of the subconductance level does not change with HC concentration and its open duration is briefer than that of full amplitude events, indicating lower open-channel stability. Dual effects are distinguished from macroscopic responses: HC reduces amplitude by acting from either open or closed states, and it increases decay rates from the open state. Thus, HC acts as a negative modulator of 5-HT type 3A receptors by different mechanisms: It acts as an open-channel blocker and it favors opening to a preexisting subconductance level. The latter constitutes a novel, to our knowledge, mechanism of channel modulation, which might be applicable to other steroids and channels.